VISUAL BASIC FOR APPLICATIONS IN SALES ADMINISTRATION TANGERANG RECORD STORES - Tini Tini; Eko Hadiyanto,SSi, MMSI Eko Hadiyanto,SSi, MMSI (Jurnal Sistem Informasi, 2002)
The definition of a computer system is a combination of some computer equipmentthat are interconnected and coordinated by an operating system.By using a computer system at the sales system on Cassette Rama Stores will carrythe advantage that it takes more labor and cost needed a little cheaper and the timerequired is shorter, more reliable and accurate data. But there is still perceived lack ofabsence tenga experts who understand the software that is used when there is an errorthat occurred. Therefore, with computerized systems more effectively and efficientlythan with manual.While the in designing a system needs a tool to simplify the design. Tools help himinclude Data Flow Diagrams (DFD), Entity Relationship Diagram ERD) andnormalization.